Railroads: Recent Books and Neglected Problems - Ripley, William Z. (Quarterly Journal of Economics, 1925)
I. The qualities a textbook should have, 152. — Estimation of Vanderblue, 156; Jones, 156; Haney, 157; Miller, 159. — II. Neglected Problems: governmental problem, 160; division of through rates, 162; terminals, 163; physical geography, 164; other fields of transportation than railroads, 165.